Visualizing hippocampal neurons with in vivo two-photon microscopy using a 1030 nm picosecond pulse laser - Kawakami, Ryosuke (Nature Publishing Group, 2013)
In vivo two-photon microscopy has revealed vital information on neural activity for brain function, even in light of its limitation in imaging events at depths greater than several hundred micrometers from the brain surface. We developed a novel semiconductor-laser-based light source with a wavelength of 1030 nm that can generate pulses of 5-picosecond duration with 2-W output power, and a 20-MHz repetition rate. We also developed a system to secure the head of the mouse under an upright microscope stage that has a horizontal adjustment mechanism. We examined the penetration depth while imaging the H-Line mouse brain and demonstrated that our newly developed laser successfully images not only cortex pyramidal neurons spreading to all cortex layers at a superior signal-to-background ratio, but also images hippocampal CA1 neurons in a young adult mouse.